The Anti-Depressive Effects of Hesperidin and the Relative Mechanisms Based on the NLRP3 Inflammatory Signaling Pathway - Xie, Lulu; Gu, Zhimin; Liu, Haizhao; Jia, Beitian; Wang, Yiyang; Cao, Min; Song, Ruiwen; Zhang, Zhaiyi; Bian, Yuhong (Frontiers in Pharmacology, 2020)
There is increasing evidence showing that inflammation is associated with depression in humans. Hesperidin, a natural bioflavonoid, has performed excellent effects on depression. The aim of this research was to investigate the therapeutic eﬀect of hesperidin on chronic unpredictable mild stress (CUMS)-induced rats. The sucrose preference test (SPT), forced swimming test (FST) and open ﬁeld test (OFT) were performed to measure the depression-related symptoms. The enzyme-linked immunosorbent assay (ELISA) were used to determine the concentrations of interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α in the prefrontal cortex (PFC) of rats and cellular supernatant. PCR and western-blot were used to monitor the differences of NLRP3, caspase-1, ASC activation in the levels of genes and proteins in the PFC of rats and microglia. The activation of microglia was determined using immunofluorescence staining and flow cytometry assay. Our results show that hesperidin treatment signiﬁcantly relieved depressive like behaviors in CUMS rats. In addition, hesperidin decreased the expression levels of IL-1β, IL-6, TNF-α, NLRP3, caspase-1 and ASC in the PFC and microglia. This study investigated that hesperidin treatment ameliorated CUMS-induced depression by suppressing microglia and inflammation.